Ethical Conduct towards Students Implied in Surah Al-Kahf (A Study of Quraish Shihab’s Tafsir Al-Misbah) - Hakiman, H (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This study revealed the ethical conduct towards students implied in the Quran, specifically Surah Al-Kahf verses 60-82, as interpreted in Quraish Shihab’s Tafsir Al-Misbah. The primary source of this library research was the Quraish Shihab’s work of Qur’anic interpretation, Tafsir Al-Misbah. Meanwhile, Tafsir al-Azhar and Tafsir al-Qurtubi were employed as the secondary sources. This study aimed at describing the ethical conduct towards students as contained in the Qur’an, specifically Surah Al-Kahf verses 60-82, based on Quraish Shihab’s Tafsir Al-Misbah. The data were collected using documentation technique and analyzed using content analysis approach. Based on the results, the ethical conduct towards students as implied in Surah Al-Kahf requires educators to be a knowledge-humble person, teach with affection, avoid overburdening students, set class rules, create constructive learning environment, be a patient educator, and present a material in small steps. It is expected that the results can be a benchmark for educators, teachers, lecturers, and religious teachers in carrying out their duties.